Spurious complexity and common standards in markets for consumer goods - Alexia Gaudeul; Robert Sugden (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
It has been argued that cognitively constrained consumers respond sub-optimally to complex decision problems, and that firms can exploit these limitations by introducing spurious complexity into tariff structures, weakening price competition. We model a countervailing force. Restricting one's choices to the most easily comparable options is a psychologically well-attested heuristic. Consumers who use this heuristic favour firms that follow common conventions about tariff structures. Because a 'common standard' promotes price competition, a firm's use of it signals that it offers value for money, validating the heuristic. This allows an equilibrium in which firms use common standards and set competitive prices.
Keywords: D83; L13; L51; 330; common standard; spurious complexity; cognitive limitations; Konsumentenverhalten; Kognition; Konsumgut; Normung; Signalling; Produktqualität; Preiswettbewerb; Theorie